Fairness and efficiency in a subjective claims problem - Anita Gantner; Rudolf Kerschbamer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
In a subjective claims problem several agents have contributed to the production of a cake which is to be divided among them. Since contributions are difficult to compare and the production function is nonlinear, agents'subjective evaluations of claims are likely to be conflicting. In a large-scale experimental study we compare the performance of three mechanisms which use agents' reports to resolve the subjective claims problem. The mechanisms differ with respect to the information they process, and they are compared in terms of efficiency and perceived allocative and procedural fairness.
Keywords: D63; C91; D61; 330; Fair Division; Subjective Claims; Experiment; Mechanisms